Peran Orang Tua dalam Pengembangan Bahasa Anak di Era Digital - Tia Nabila; Nurfitria Nurfitria; Mufaro’ah Mufaro’ah (Institut Nalanda, 2024)
Early childhood special needs include language development, which is crucial for effective communication. It is recommended to enhance language comprehension (receptive language) before developing speaking skills (expressive language). The ability to speak serves as a means to communicate ideas, thoughts, and emotions to others. The digital age is characterized by the presence of technology that brings increased speed and flow of knowledge in the economy and society. Parents living in an information-rich community environment realize that children in the digital era cannot be separated from the use of technology in their daily lives. The development of digital technology has entered various stages of development that should be achieved by children. Technological advancements have provided them with convenience in living life more quickly and efficiently. Therefore, this paper will review how early childhood language development, in terms of listening and speaking, is impacted in the digital era.